2016
DOI: 10.1089/lap.2016.0342
|View full text |Cite
|
Sign up to set email alerts
|

The First Case Report of Robotic Multivisceral Resection for Synchronous Liver Metastasis from Pancreatic Neuroendocrine Tumor: A Case Report and Literature Review

Abstract: Liver metastases in PNETs are considered an adverse factor. Aggressive surgical management is a mainstay. The laparoscopic approach to pancreatic or hepatic surgery is difficult in inexperienced hands with steep learning curve. The recent robotic system seems to overcome many limitations. This is the first case of robotic multivisceral resection for synchronous liver metastasis from PNET. Concurrent primary tumor resection with hepatectomy offers potential curative intention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Twenty-seven non-comparative studies reported on outcomes from da Vinci robotic surgeries performed with ELS; of these, 18 were with the Echelon ELS and 9 with the Endo GIA ELS. Robotic surgery performed with ELS is generally referred to as an advanced surgical technique for multiple types of procedures, including gastric bypass [1012, 28], sleeve gastrectomy [1215], liver resection [18, 19, 30, 31], colorectal surgery [2024, 32–34], thoracic surgery [25], nephrectomy [26, 35], pancreatectomy [27], bladder surgery [34], and prostate surgery [36]. These procedures typically take longer than laparoscopic or open surgery [10, 11, 13, 14, 18], but have comparable or lower complication rates and/or more favorable perioperative outcomes [1114, 25, 27, 36].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…Twenty-seven non-comparative studies reported on outcomes from da Vinci robotic surgeries performed with ELS; of these, 18 were with the Echelon ELS and 9 with the Endo GIA ELS. Robotic surgery performed with ELS is generally referred to as an advanced surgical technique for multiple types of procedures, including gastric bypass [1012, 28], sleeve gastrectomy [1215], liver resection [18, 19, 30, 31], colorectal surgery [2024, 32–34], thoracic surgery [25], nephrectomy [26, 35], pancreatectomy [27], bladder surgery [34], and prostate surgery [36]. These procedures typically take longer than laparoscopic or open surgery [10, 11, 13, 14, 18], but have comparable or lower complication rates and/or more favorable perioperative outcomes [1114, 25, 27, 36].…”
Section: Results Of the Literature Searchmentioning
confidence: 99%
“…It should be stressed that the CUSA system, the most useful instrument in laparoscopic liver surgery, cannot be applied in robotic surgeries. [45] In addition, medical insurance does not cover the relatively high expense, which limits the development of robotic surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…With growing experience and adoption of robotic distal pancreatectomy, several authors have published combined pancreatectomy and hepatectomy. Calin et al [ 26 ] published the first case report of a combined robotic distal pancreatectomy and hepatectomy for neuroendocrine tumor (NET) metastatic to the liver. The operative time for this combined procedure was 369 min with an EBL of 100 mL.…”
Section: Combined Hepatic and Other Abdominal Solid Organ Resectionmentioning
confidence: 99%